Features of a new Coronavirus infection in children of different ages - M. A. Shakmaeva; T. M. Chernova; V. N. Timchenko; T. A. Nachinkina; K. V. Tetyushin; T. A. Kaplina; M. D. Subbotina; O. V. Bulina; O. I. Afanasyeva (Детские инфекции (Москва), 2021)
The new coronavirus infection (COVID-1 9) is a socially significant problem around the world. According to available statistics, complications are less common among children, asymptomatic or mild forms of the disease prevail more often.This article presents the features of the viral landscape of the upper respiratory tract in children with ARVI in a pandemic, the clinical and laboratory features of the course of COVID-1 9 in children of different ages.It was found that SARS-CoV-2 is detected only in a third (32.9%) of hospitalized patients with respiratory symptoms, in 4.3% of cases — in combination with seasonal CoV-OC43 / CoV-229E, in 1 1.6% — with other respiratory viruses. The most frequent source of infection with the SARS-Cov-2 were family members. Children with a moderate form of the disease predominated among the patients. The leading symptoms of COVID-19 were fever, catarrhal symptoms, as well as gastrointestinal manifestations and anosmia. A feature of the new coronavirus infection in newborns and children of the first month of life was the absence of fever and intoxication, the lack of expression of catarrhal manifestations when the colon is involved in the pathological process (colitis, rarely — hemocolitis). In the compete blood test in children under the age of one year, monocytosis prevailed, in children over 7 years old — leukopenia and accelerated ESR. Among the changes in the biochemical analysis of blood, the most common was an increased C-reactive protein.